The Influence of Socio-economy and Local Food Diversity on Stunting in Toddlers - Husnul Khotimah; Santi Sundary Lintang; Fadhila Azkiya (Consilium Sanitatis: Journal of Health Science and Policy, 2023)
Objective: Stunting is still a big challenge faced by this nation even in the world even though it can actually be prevented. This study aims to determine the socio-economic relationship (mother's education, father's education, family income) to the incidence of stunting and to find out the phenomenon of providing local food diversity to toddlers with stunting. Methods: The research design is a mixed method. The quantitative design used in this study is a cross-sectional approach, while the qualitative design uses an intrinsic case study design. The sample in this study was 100 toddlers. The sampling technique was purposive sampling. Data analysis in quantitative using chi square. Qualitative study using the study of phenomena with in-depth interviews. Results: There was a significant relationship between mother's education (p=0.003) and father's education (p=0.045) and the incidence of stunting in toddlers, but there was no significant relationship between family income (p=0.678) and the incidence of stunting in toddlers. All respondents did not know how to process local wisdom-based food ingredients into nutrient-rich foods and did not provide a variety of foods to their children, and did not pay attention to the balanced nutritional content that was right for their children. Conclusion: There is a need for structured and continuous education to increase public knowledge about stunting and how to provide a variety of foods.